The Functioning of The Differential Items on The Physics Learning Result Test Device at MAN Tegal City - Tri Setiya Titi Utami; Purwo Susongko; Suriswo Suriswo (Universitas Pancasakti Tegal, 2022)
This study aims to (1) analyze the characteristics of the physics questions tested at MAN Tegal City, (2) find out which questions were detected with DIF (3) analyze the confidence plot on the test items for the end of the 2020/2021 school year assessment test. at MAN Tegal City. The population in this study were all students of MAN Tegal City. As for the sample, all the answer sheets of students who took the final assessment test for the 2020/2021 school year on physics subjects consisting of 337 answer sheets. Data collection is by using the documentation method. The analysis technique uses Rasch modeling with Wald test. From the results of this study, it was concluded that (1) there were characteristics in the form of differences in the level of difficulty of the final assessment items for the 2020/2021 school year in physics subjects tested on class XI students at MAN Tegal City, (2) the results of the DIF detection analysis using the Wald test. shows empirical facts that in the final assessment test kit for the 2020/2021 school year physics class XI at MAN Tegal City there are no questions containing DIF, (3) the confidence plot can be used properly on the test kit.